2001
DOI: 10.1103/physrevlett.87.216402
|View full text |Cite
|
Sign up to set email alerts
|

Charged Excitons in the Fractional Quantum Hall Regime

Abstract: We study the photoluminescence spectrum of a low-density (nu<1) two-dimensional electron gas at high magnetic fields and low temperatures. We find that the spectrum in the fractional quantum Hall regime can be understood in terms of singlet and triplet charged excitons. We show that these spectral lines are sensitive probes for the electron compressibility. We identify the dark triplet charged exciton and show that it is visible at the spectrum at T<2 K. We find that its binding energy scales as 0.1e(2)/l, whe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
129
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(138 citation statements)
references
References 27 publications
8
129
1
Order By: Relevance
“…Also the predicted singlettriplet crossing was reported recently [34]. In this paper we summarize our results [7], which, concerning the PL experiments are consistent with the observations of Yusa et al [6], i.e., (i) we observe a charged exciton at very low temperatures, which is not present in the spectrum at T = 2 K, (ii) this exciton occurs for filling factor ν < 1/3 only, i.e., related to the fractional quantum Hall effect (FQHE) regime, and (iii) the PL intensity of this excitation is of similar strength to that of the singlet exciton. Figure 2 shows a comparison of left-circularly polarized PL spectra, which were recorded at T = 2 K (upper spectrum), and at T = 0.1 K (lower spectrum).…”
Section: Methodssupporting
confidence: 81%
See 4 more Smart Citations
“…Also the predicted singlettriplet crossing was reported recently [34]. In this paper we summarize our results [7], which, concerning the PL experiments are consistent with the observations of Yusa et al [6], i.e., (i) we observe a charged exciton at very low temperatures, which is not present in the spectrum at T = 2 K, (ii) this exciton occurs for filling factor ν < 1/3 only, i.e., related to the fractional quantum Hall effect (FQHE) regime, and (iii) the PL intensity of this excitation is of similar strength to that of the singlet exciton. Figure 2 shows a comparison of left-circularly polarized PL spectra, which were recorded at T = 2 K (upper spectrum), and at T = 0.1 K (lower spectrum).…”
Section: Methodssupporting
confidence: 81%
“…In a subsequent work, Szlufarska et al found that in asymmetric quantum wells the singlet-triplet crossing can be at considerably lower fields [33]. In experiments at very low temperatures the dark triplet exciton was identified by Yusa et al [6] and Schüller et al [7]. Also the predicted singlettriplet crossing was reported recently [34].…”
Section: Methodsmentioning
confidence: 85%
See 3 more Smart Citations